If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4+4g=-2+6g
We move all terms to the left:
4+4g-(-2+6g)=0
We add all the numbers together, and all the variables
4g-(6g-2)+4=0
We get rid of parentheses
4g-6g+2+4=0
We add all the numbers together, and all the variables
-2g+6=0
We move all terms containing g to the left, all other terms to the right
-2g=-6
g=-6/-2
g=+3
| -4m+10=-m-8 | | D=7/6(m-55) | | -(x+6)=22 | | -1+2x=43 | | 2(p+5)7=4p | | 5y=4y-20 | | 2s=3s−10 | | 6−3t=-2t | | s+7s+20=47 | | s+7+20=47 | | 4/3y+25=33 | | t−4=−9 | | 2(x-1)=56 | | a-15=4a=3 | | 2=0.05x+0.40x | | 9y-(5y+3)=7 | | w-9.21=4.1 | | 2(h+1=5h+7 | | 12x-3=8x+8 | | b+8=27 | | 6(2x-10)=8(x+2) | | k/0.32=2 | | 56+4w=11w | | 2/2/3+3n=4/5n+15 | | 3x-4+4=5+4 | | 18+y=3y | | 2x+23=2/9x | | -18-(x/4)=-20 | | -5x+103=63 | | 4x-3+9x=3x-9 | | 3x-71=86 | | x-8+6x=-43 |